the Distribusi Fungsi Konseptual, Sosial, dan Operasional dalam Struktur Manajemen Pendidikan: Distribusi Fungsi Konseptual, Sosial, dan Operasional dalam Struktur Manajemen Pendidikan - Hidayat Mustafid (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
The effectiveness of educational management is largely determined by the clarity and balance of managerial function distribution within organizational structures. In practice, inappropriate role mapping often leads to overlapping responsibilities, weakened strategic decision-making, and the dominance of operational activities that marginalize conceptual and social functions. This study aims to analyze the distribution of conceptual, social, and operational functions in educational management structures and examine their implications for organizational effectiveness. A qualitative approach employing a literature review method was used through a systematic examination of educational management textbooks and relevant national and international journal articles. The analysis compares theoretical perspectives and empirical findings concerning managerial roles across different levels of educational organizations. The findings indicate that conceptual and operational functions vary proportionally according to structural levels, whereas social functions remain universal and inherent at all managerial levels. Balancing these three functions is essential for achieving effective, adaptive, and sustainable educational management.